2020
DOI: 10.33151/ajp.17.826
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Review of Pandemic Studies in Paramedicine

Abstract: Introduction The spread of COVID-19 has challenged the paramedic community’s ability to provide health care, maintain personal safety, and implement evidence informed decisions and programs. The study objective was to examine the published literature related to paramedicine and pandemics. Methods A rapid review of research derived from an existing broad database of literature generated between 2006 and 2019 was used. We conducted a targeted secondary search of this database to identify studies of pandemics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Studies have reported that extensive and regular training for pandemics (e.g. mandatory yearly competency-based training and education programs with skill based drills) would enable nurses and paramedics to feel more prepared and confident in their abilities in care for patients [36] , [37] , [38] , [39] . In addition, clear leadership and clear directives from management early on in the pandemic is critical to preparedness and planning [40] , [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that extensive and regular training for pandemics (e.g. mandatory yearly competency-based training and education programs with skill based drills) would enable nurses and paramedics to feel more prepared and confident in their abilities in care for patients [36] , [37] , [38] , [39] . In addition, clear leadership and clear directives from management early on in the pandemic is critical to preparedness and planning [40] , [41] .…”
Section: Discussionmentioning
confidence: 99%
“…While the ongoing COVID-19 pandemic has increased virtual care and telehealth delivery by paramedic services [34,35], we still lack a clear understanding of the role of paramedics as virtual care providers, primary care extenders, and facilitators of virtual care visits. The COVID-19 pandemic further emphasized the benefits of keeping people out of hospital if they can be cared for at home or in their community [34].…”
Section: Discussionmentioning
confidence: 99%
“…While the ongoing COVID-19 pandemic has increased virtual care and telehealth delivery by paramedic services [33,34], we still lack a clear understanding of the role of paramedics as virtual care providers, primary care extenders, and facilitators of virtual care visits. The COVID-19 pandemic further emphasized the benefits of keeping people out of hospital if they can be cared for at home or in their community [33].…”
Section: Discussionmentioning
confidence: 99%